Perforating eye injury in Allegheny County, Pennsylvania. - Landen, D (1990)
From 1980 through 1986, acute perforating eye injury (ICD codes 871.0-871.9) was diagnosed in 345 residents of Allegheny County, Pennsylvania. The mean incidence rate was 3.49 per 100,000 person years. There was no significant change in incidence over the seven-year period. The largest number of injuries occurred among individuals working with tools, of which 47 percent were occupational. Males had a 6.5-fold risk of injury relative to females. Blacks had a risk of 2.2 times that of Whites, mainly due to an excess of assaultive injuries. Individuals who had had recent ocular surgery accounted for 4.6 percent of cases overall, and for 31.6 percent of cases in those over age 60.